Efeitos do exercício isométrico sobre os índices de pressão arterial e frequência cardíaca em adultos : meta-análises - Vieira, Izabella de Oliveira (2017)
The effects of isometric exercises on blood pressure (BP) and heart rate (HR) indexes have been investigated. However, the samples are usually reduced, which makes it difficult to generalize the data. Systematic reviews with meta-analyzes are presented as alternatives because it allows the grouping of data from different studies. Thus, the objective of this study was to evaluate the influence of age on acute PA and HR changes in adults generated by isometric exercise (Study I), as well as to investigate the chronic effects on these same parameters (Study II). To do so, we searched the PubMed, Lilacs, Scopus and PeDro databases for clinical trials published until May 23, 2016 that evaluated changes in BP and HR in adults after isometric exercises and performed with subjects> 18 years. The studies that studied the responses after an isometric exercise session were selected and separated according to the age of the sample, <and> 60 years, to analyze the influence of age on the acute effect. Those with intervention period ≥4 weeks were selected for chronic effect assessment. Thus, 4 articles were included in study I and, although half of the studies were performed with adults and the other with the elderly, the direct comparison of the studies was not performed, due to divergences between the exercise characteristics used. In study II, 2 studies were identified that demonstrated that isometric manual grip training is able to significantly reduce SBP and MAP only, -1.58 [-2.64, -0.51], p = 0.004, and -0.91 [-1.58, -0.24], p = 0.008, respectively, after an intervention period of 8-10 weeks. Thus, it was observed a need to produce studies that seek to evaluate the acute responses to isometric exercise protocols with similar characteristics used in current chronic training programs, especially in the elderly and hypertensive, so that questions about risk and differences between Populations are identified. In addition, isometric manual grip training significantly reduces systolic BP and mean BP of adults. However, studies with different samples and modalities of different isometries are still necessary to safely subsidize the use of this training modality in the management of hypertension.